Energy flow though a dairy farm in a village dairy cooperative in the Tarai area of Uttaranchal Himalayas - SINGH, VIR; TRIPATHI, RAJAN KUMAR; CHAUHAN, S S; KUMAR, ANIL (The Indian Journal of Animal Sciences, 2014)
Energy flow pattern in a dairy farm in a village dairy cooperative (VDC) in the Tarai area of Uttaranchal Himalayas was quantitatively analysed. Feed contributed as much as 73% of the total energy flow, of the total output energy, dung accounted fpr as much as 70% and milk 30% negligible amount of energy (only 0.1%) was contained in the new born calves. The energy balance of a dairy farm suggests that dung is the most important product of a dairy farm. Though milk is regarded as the most important product and virtually the only target of dairy production, dung is the largest proportion of the dairy outputs of a dairy farm. Gross energetic efficiency of a dairy farm in a VDC comes out to be 37%. This would suggest that dairy farm is able to efficienty utilize only 37% of the energy and the rest 63% is being used for purposes other than production. Energetic efficiency is an important indicator to measure that performance of a dairy farm in relation to the environment or the farming system it operates in. Improvement in dairy farming efficiency will take place with the increase in outputs relative to inputs. Improvement in the productivity of the ecosystem a dairy farm s part of will have impact on the performance of a dairy farm. Dairy farm linkages with the farming system components-especially with households and cropland in the context of the Tarai area-need to be ameliorated so that the energy flow pattern in the ecosystem/farming system is maintained in a way that should lead to enhance productvity of the system.